ChemInform Abstract: Reactivity and Catalysis by Nanoalloys. Issue 44 (14th October 2013) - Bazin, Dominique; Fechete, Ioana; Garin, Francois; Barcaro, Giovanni; Negreiros, Fabio R.; Sementa, Luca; Fortunelli, Alessandro
Abstract Review: 330 refs.